Effective fecal microbiota transplantation for recurrent Clostridioides difficile infection in humans is associated with increased signalling in the bile acid-farnesoid X receptor-fibroblast growth factor pathway. (4th March 2019) - Monaghan, Tanya; Mullish, Benjamin H; Patterson, Jordan; Wong, Gane KS; Marchesi, Julian R; Xu, Huiping; Jilani, Tahseen; Kao, Dina
ABSTRACT: The mechanisms of efficacy for fecal microbiota transplantation (FMT) in treating recurrent Clostridioides difficile infection (rCDI) remain poorly defined, with restored gut microbiota-bile acid interactions representing one possible explanation. Furthermore, the potential implications for host physiology of these FMT-related changes in gut bile acid metabolism are also not well explored. In this study, we investigated the impact of FMT for rCDI upon signalling through the farnesoid X receptor (FXR)-fibroblast growth factor (FGF) pathway. Herein, we identify that in addition to restoration of gut microbiota and bile acid profiles, FMT for rCDI is accompanied by a significant, sustained increase in circulating levels of FGF19 and reduction in FGF21. These FGF changes were associated with weight gain post-FMT, to a level not exceeding the pre-rCDI baseline. Collectively, these data support the hypothesis that the restoration of gut microbial communities by FMT for rCDI is associated with an upregulated FXR-FGF pathway, and highlight the potential systemic effect of FMT.